2015
DOI: 10.1021/acsami.5b06548
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Transmission Electron Microscopy Observation of the Lithiation–Delithiation Conversion Behavior of CuO/Graphene Anode

Abstract: The electrochemical conversion behavior of metal oxides as well as its influence on the lithium-storage performance remains unclear. In this paper, we studied the dynamic electrochemical conversion process of CuO/graphene as anode by in situ transmission electron microscopy. The microscopic conversion behavior of the electrode was further correlated with its macroscopic lithium-storage properties. During the first lithiation, the porous CuO nanoparticles transformed to numerous Cu nanograins (2-3 nm) embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Advanced ex and in situ measurements have promoted fundamental understanding of the structural and morphological modifications along with the effects of metal oxide composition on the conversion reaction features . Among the various investigative approaches, three‐dimensional imaging at the micro‐ and nanoscale may actually shed light on the particle evolution throughout the lithium‐exchange process and reveal crucial morphological parameters for electrode modelling, such as the phase volume fraction and the particle size distribution .…”
Section: Introductionsupporting
confidence: 68%
“…Advanced ex and in situ measurements have promoted fundamental understanding of the structural and morphological modifications along with the effects of metal oxide composition on the conversion reaction features . Among the various investigative approaches, three‐dimensional imaging at the micro‐ and nanoscale may actually shed light on the particle evolution throughout the lithium‐exchange process and reveal crucial morphological parameters for electrode modelling, such as the phase volume fraction and the particle size distribution .…”
Section: Introductionsupporting
confidence: 68%
“…According to previous reports on composite conversion anodes, [38,41] the first cycle shows irreversible processes relatedt ot he formation of aS EI and structural rearrangements within the material, in additiont ot he reversible lithiation of CuO, Fe 2 O 3 ,a nd carbon matrix. [26][27][28] This processm ay cause limited reversibility and remarkable changes in particles ize;s ubsequently,t he electrode structure stabilizes throughout cycling. [53] Ac arbon delithiationp rocess at about 0.3 Vv ersus Li + /Li and deconversion reactions above 1Vversus Li + /Li are observed throughout the first anodic scan.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the first cathodic scan reveals two peaks at 1.1 and 0.7 Vv ersus Li + /Li, which reflect the reduction of CuO [38] and Fe 2 O 3 [41] to Cu, Fe, and Li 2 O, followed by ab road signal below 0.4 Vv ersus Li + /Li, which suggestsl ithium insertion into carbon. [26][27][28][29] Similarly, electron microscopy,X RD, and X-ray photoelectron spectroscopy (XPS) studies have shown that Fe 2 O 3 exchanges lithium ions through insertion followed by conversion to metallic Fe embedded within aL i 2 Om atrix, which leads to significant electrode swelling upon lithiation. The CV profile stabilizes in subsequent cycles and reveals reversible lithium conversion within the range of 0.7 to 2.5 Vv ersus Li + /Li andl ithium insertion into the carbon matrixb elow 0.3 Vv ersus Li + /Li.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the supernatant from a previous process was retained and then used for the subsequent preparation of porous Fe 3 O 4 nanocrystals composed of small grains. When the nanoparticle is interconnected with small grains, this nanoparticle is generally denoted as a porous nanoparticle . A mixture of Fe(acac) 3 (100 g) and the first recycled solvent (the first supernatant) was heated to 300°C and maintained at this temperature for 30 min.…”
Section: Resultsmentioning
confidence: 99%